KAJIAN ANALISIS KARAKTERISTIK PARKIR OFF-STREET KENDARAAN ANGKUTAN BARANG DAN PENGANTARAN BARANG DI PUSAT PERBELANJAAN PASAR JATINEGARA - Evriyani, Desy; Nahry, Nahry; Soehodho, Sutanto (FSTPT Indonesia, 2015)
Pasar Jatinegara as one of the shopping center for retailer in Jakarta has a problem with parking lot issue. As a wholesale shopping center, the parking lot is dominated by freight transport. This situation is getting worse due to on-street parking restriction during working days start from 17th June 2013. It caused the capacity of parking decreases. This research is aimed to analyze parking characteristic of freight and goods conveyance at Pasar Jatinegara. The characteristic of off-street parking such as accumulation, volume, duration, turn over, parking index, index of parking activity (IAP), and V/C ratio indicates that the performance of parking service before and after the regulation is still not sufficient. Meanwhile the characteristics of goods conveyance and stores delivery are still bad. There are few solutions proposed in order to improve the performance of off-street parking and goods conveyance.